2009
DOI: 10.1093/nar/gkp1153
|View full text |Cite
|
Sign up to set email alerts
|

RepD-mediated recruitment of PcrA helicase at the Staphylococcus aureus pC221 plasmid replication origin, oriD

Abstract: Plasmid encoded replication initiation (Rep) proteins recruit host helicases to plasmid replication origins. Previously, we showed that RepD recruits directionally the PcrA helicase to the pC221 oriD, remains associated with it, and increases its processivity during plasmid unwinding. Here we show that RepD forms a complex extending upstream and downstream of the core oriD. Binding of RepD causes remodelling of a region upstream from the core oriD forming a ‘landing pad’ for the PcrA. PcrA is recruited by this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This multi-functionality is reflected in the ability of UvrD/PcrA to interact physically and functionally with many different partner proteins including UvrB, MutL, MutS, RecA and RepC/D (1320). We and others have recently shown that PcrA/UvrD also interacts with RNA polymerase (RNAP) (1,14,21), and this interaction could be important for the UvrD-dependent backtracking of stalled RNA polymerase (1).…”
Section: Introductionmentioning
confidence: 99%
“…This multi-functionality is reflected in the ability of UvrD/PcrA to interact physically and functionally with many different partner proteins including UvrB, MutL, MutS, RecA and RepC/D (1320). We and others have recently shown that PcrA/UvrD also interacts with RNA polymerase (RNAP) (1,14,21), and this interaction could be important for the UvrD-dependent backtracking of stalled RNA polymerase (1).…”
Section: Introductionmentioning
confidence: 99%
“…One such partner of PcrA is RepD, a plasmid replication initiator protein that recognizes and forms a covalent adduct with the oriD sequence of the plasmid, and then recruits PcrA for processive unwinding (24, 25). We prepared an oriD DNA-RepD adduct, and measured the intramolecular conformation of PcrA bound to this adduct (18).…”
mentioning
confidence: 99%
“…The recruitment of the helicase onto the replication initiation site has also been shown by footprinting experiments using exonuclease (Exo) III (173). RepD binding to oriD creates an area of protection to ExoIII digestion which extends beyond the oriD region: ∼74 to 80 bp upstream of ICR I for the continuous strand and ∼46 to 50 bp downstream of ICR III for the nicked strand (173), although further resistance points can be found within the oriD, after longer digestion times.…”
Section: Role Of Superfamily Group 1 Helicases and Their Interaction mentioning
confidence: 90%
“…Furthermore, these three stages of protein loading on the DNA have been studied by atomic force microscopy, where RepD appears as a globular particle which bends the DNA fragment around 90°in 39% of the oriD fragments analyzed. However, when both proteins were bound to the DNA, the proportion of bent DNA increased up to 60%, while ADPNP decreased this percentage to 41% (173).…”
Section: Role Of Superfamily Group 1 Helicases and Their Interaction mentioning
confidence: 94%
See 1 more Smart Citation